2008
DOI: 10.2106/jbjs.g.01192
|View full text |Cite
|
Sign up to set email alerts
|

Nonunions and the Potential of Stem Cells in Fracture-Healing

Abstract: Recent progress in human embryonic and adult stem cell research is a cause for much enthusiasm in bone and joint surgery. Stem cells have therapeutic potential in the realm of orthopaedic surgery because of their capacity to self-renew and differentiate into various types of mature cells and tissues, including bone. Because nonunions remain a clinically important problem, there is interest in the use of cell-based strategies to augment fracture repair. Such strategies are being investigated with variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 55 publications
1
98
0
Order By: Relevance
“…A reduced pool of human bone marrow stromal/stem cells (BMSCs) correlates with altered bone repair in patients with fracture nonunions (5,6). The administration of BMSCs has shown promise in treating patients with fracture nonunions in some settings (7)(8)(9)(10)(11)(12). Interestingly, recent studies using reporter-tagged BMSCs have demonstrated that transplanted BMSCs specifically localize within the fracture gap and intramedullary or internal calluses rather than within the external callus tissues mostly derived from the periosteum and surrounding soft tissue, suggesting a localized and specific role for BMSCs in fracture repair (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…A reduced pool of human bone marrow stromal/stem cells (BMSCs) correlates with altered bone repair in patients with fracture nonunions (5,6). The administration of BMSCs has shown promise in treating patients with fracture nonunions in some settings (7)(8)(9)(10)(11)(12). Interestingly, recent studies using reporter-tagged BMSCs have demonstrated that transplanted BMSCs specifically localize within the fracture gap and intramedullary or internal calluses rather than within the external callus tissues mostly derived from the periosteum and surrounding soft tissue, suggesting a localized and specific role for BMSCs in fracture repair (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, autologous bone marrow injection enhances cellular numbers and stimulates the cells to fabricate a structural osteoconductive substrate with extremely low donor site morbidity (Pountos, 2010). Bone marrow injection is a mini-invasive technique and can contribute to bone union in cases of stable delayed or nonunion (Bhutia, 2015;Singh, 2013;Tseng, 2008). It has reduced soft tissue damage, improved the recovery period, and minimized scaring.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are traumatic situations in which bone fails to regenerate itself leading to non-union [22] . While there is no universally accepted definition, non-union refers to a fracture that has not united within 6 to 9 months after fracture onset and that requires additional surgical or non-surgical intervention.…”
Section: Rationale Of Cell Therapy For Fracture Repairmentioning
confidence: 99%